Adsorption Properties of Activated Carbons Prepared from Recycled PET in the Removal of Organic Pollutants from Aqueous Solutions - Isabel P.P. Cansado; Cristina Galacho; Ângela S. Nunes; Manuela L.R. Carrott; Peter J.M. Carrott (Adsorption Science & Technology, 2010)
Activated carbons (ACs) were prepared from recycled polyethylene terephthalate (PET) by chemical activation with KOH and used successfully for the removal of 4-chloro-2-methylphenoxyacetic acid (MCPA) and Methylene Blue (MB) from aqueous media. In order to improve the adsorption capacity towards pollutant removal, the AC was submitted to different post-treatments. After oxidation, the sample exhibited an increase in MB adsorption capacity but showed a decreased MCPA adsorption removal extent. High-temperature treatment was not favourable for increasing the MB or MCPA adsorption capacity. However, after treatment with sodium hydroxide or urea, the samples showed a significant increase in their MCPA adsorption capacities. Normalisation of the MB and MCPA adsorption data with respect to the micropore volume led to a clearer understanding of the influence of the textural and chemical characteristics of the AC on the removal of MB and MCPA. The MB and MCPA adsorption isotherms were analysed via the Langmuir and Freundlich models, with the calculated parameters accurately fitting the experimental data and exhibiting good agreement between them.